Monochromatic Light Interactions in the Early Hypocotyl Elongation of Sunflower (Helianthus annuus L.) Seedlings - Dragan Vinterhalter; Vaclav Motyka; Branka Vinterhalter (International Journal of Plant Biology)
Sunflower is a crop species well adapted for cultivation in open fields under full sunlight. Young plantlets can be grown in growth chambers under low irradiance, where different aspects of light can be easily tracked. Using time-lapse imaging, we have shown how monochromatic red, blue, and far-red light and their combinations interacted, affecting the rhythmicity and elongation of sunflower hypocotyls. Monochromatic light of any color, applied individually, canceled all manifestations of diurnal rhythmicity and anticipation of imminent light transitions present in diurnal photoperiods established by white LED light panels. Monochromatic light also significantly increased the rate of hypocotyl elongation, which became uniform (arrhythmic) and often triggered the appearance of guttation. The rate of hypocotyl elongation was highest with the blue light and lowest with red light. In double light combinations, red light suppressed the stimulative effect of blue light, but it promoted the elongation rate when used together with far-red light. A triple light combination of red, blue, and far-red light stimulated hypocotyl elongation to a high degree and increased the elongation rate more than twofold compared with red and fourfold compared with white LED light.